Nanoscale Chemical Imaging of a Single Catalyst Particle with Tip-Enhanced Fluorescence Microscopy - Kumar, Naresh; Kalirai, Sam; Wain, Andrew J.; Weckhuysen, Bert M. (Wiley, 2019)
Determining the active site in real-life solid catalysts remains anintellectual challenge and is crucial for exploring the roadtowards their rational design. In recent years various micro-spectroscopic methods have revealed valuable structure-activitydata at the level of a single catalyst particle, even under reactionconditions. Herein, we introduce Tip-Enhanced FLuorescence(TEFL) microscopy as a novel and versatile characterization toolfor catalysis research. This has been achieved using a FluidCatalytic Cracking (FCC) catalyst as showcase material. Thinsectioning of industrially used FCC particles together withselective staining of Brønsted acidity has enabled high-resolution TEFL mapping of different catalyst regions. Hyper-spectral information gained via TEFL microscopy reveals aspatial distribution of Brønsted acidity within individual zeolitedomains in different regions of the FCC catalyst particle.Comparison of TEFL measurements from different FCC particlesshowed significant intra- and inter-particle heterogeneities bothin zeolite domain size and chemical reactivity
Keywords: heterogeneous catalysis; fluid catalytic cracking; tip-enhanced fluorescence microscopy; nanoscale chemical imaging; acidity